Food Fraud Prevention using a Blockchain-Based System: Case Study Slaughterhouse in Sidoarjo - Daniel Soesanto; Liliana L; Bambang Prijambodo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
Data consistency and security are the most important thing to pay attention to in the supply chain of foodstuffs derived from livestock. However, the length of the existing supply chain and the lack of facilities to store and maintain the correctness of livestock data are problems in ensuring the security of the data. The use of blockchain in livestock has existed in Indonesia, but its scope is only to agriculture or only a tiny part of the livestock supply chain. Therefore, this research was conducted to develop the application of a blockchain-based livestock supply chain system in Indonesia. This research begins with conducting a literature study, analyzing the slaughterhouses. Then the development of a blockchain system for the food supply chain was carried out. System validation was carried out through interviews with the head of the slaughterhouses, breeders, and wholesalers. The results state that the system helps ensure the security of food supply chain data from livestock. However, the problem that has not been resolved is the validation process of data on the weight loss of foodstuffs in the supply chain process. This technique is expected to be used for halal certification in the future.